SARCOPTES SCABIEI INFECTION ACCOMPANIED BY HYPOCHROMIC MICROCYTIC ANEMIA IN A DOMESTIC DOG - Gusti Ayu Putu Ratih Puspasari; Sri Kayati Widyastuti; I Gusti Made Krisna Erawan (Buletin Veteriner Udayana, 2025)
Scabies is a skin infection caused by ectoparasites of the mite type, Sarcoptes scabiei. These mites infect the host's skin by making tunnels in the epidermis layer which will cause itching. This article aims to describe the occurrence of scabiosis due to Sarcoptes scabiei infection in local dogs. A series of examinations to determine the diagnosis, and the therapy given. A case study was conducted on a local male dog, named Boby, aged 4 months who had itching all over his body that had lasted for one month. Physical examination found alopecia, scales, and crusts on the head, hind legs, front legs, both ears, abdomen, back, and tail. Examination using the skin scraping method found Sarcoptes scabiei mites. Hematological examination showed that the case animal had lymphocytosis, monocytosis, granulocytopenia, hypochromic microcytic anemia, and thrombocytosis. Based on anamnesis, clinical examination results, and supporting examinations, the case animal was diagnosed with scabiosis with a prognosis of fausta. The case dog was given causative therapy in the form of ivermectin at a dose of 0.2 mg/kg BW, subcutaneous injection with two administrations at an interval of 28 days, Symptomatic therapy was given subcutaneous injection of diphenhydramine HCl at a dose of 3 mg/kg BW with two administrations at an interval of 28 days, chlorpheniramine maleate at a dose of 0.5 mg/kg BW orally for 14 days. Supportive therapy B-complex was given 1 tablet once a day for 21 days, fish oil as much as 1 tablet once a day for 20 days, and bathed with shampoo containing sulfur (twice a week). The results of treatment for 28 days showed changes in the condition of the case dog improving, pruritus, crusts, scales, lichenification began to decrease. On the 40th day the case dog showed new hair growth. The awareness of pet owners, especially those who keep dogs, must be increased by always maintaining the cleanliness of their dog's cage, eating utensils, and play equipment.